Samuel J. Baird papers - Baird, Samuel J. (Samuel John), 1817-1893.
Correspondence and miscellaneous material relating to Presbyterian Church affairs and doctrinal questions, the work of the American Bible Society in Virginia (1865-1875), and the Baird family. Includes letters concerning Baird's efforts to minister to soldiers and to assist wounded soldiers and prisoners during the Civil War. Correspondents include James W. Alexander, E. Thompson Baird, Thomas Dickson Baird, William Logan Baird, Henry A. Boardman, John Breckinridge, Robert J. Breckinridge, William C. Cattell, Jeremiah Chamberlain, John T. Duffield, Robert Smith Finley, P. D. Gurley, Mark Hopkins, George Howe, Edward P. Humphrey, Richard McIlwaine, John Miller, John W. Nevins, Theodore Sutton Parvin, William S. Plummer, Stacy G. Potts, Hugh Reid, Stuart Robinson, William Greenough Thayer Shedd, Henry B. Smith, William B. Sprague, William J. R. Taylor, T. D. Witherspoon, and James Wood.
Presbyterian clergyman and author of Newark, Ohio.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Collection material in English.
Keywords: Alexander, James W. -- 1804-1859 -- Correspondence; Baird, E. Thompson -- 1821-1887 -- Correspondence; Baird, Thomas Dickson -- Correspondence; Baird, William Logan -- Correspondence; Boardman, Henry A. -- 1808-1880 -- Correspondence; Breckinridge, John, -- 1797-1841 -- Correspondence; Breckinridge, Robert J. -- 1800-1871 -- Correspondence; Cattell, William C. -- 1827-1898 -- Correspondence; Chamberlain, Jeremiah, -- 1794-1851 -- Correspondence; Duffield, John T. -- 1823-1901 -- Correspondence; Finley, Robert Smith, -- 1804-1860 -- Correspondence; Gurley, P. D. -- 1816-1868 -- Correspondence; Hopkins, Mark, -- 1802-1887 -- Correspondence; Howe, George, -- 1802-1883 -- Correspondence; Humphrey, Edward P. -- 1809-1887 -- Correspondence; McIlwaine, Richard, -- 1834- -- Correspondence; Miller, John, -- 1819-1895 -- Correspondence; Nevins, John W. -- Correspondence; Parvin, Theodore Sutton, -- 1817-1901 -- Correspondence; Plummer, William S. -- Correspondence; Potts, Stacy G. -- 1799-1865 -- Correspondence; Reid, Hugh -- Correspondence; Robinson, Stuart, -- 1814-1881 -- Correspondence; Shedd, William G. T. -- 1820-1894 -- Correspondence; Smith, Henry Boynton, -- 1815-1877 -- Correspondence; Sprague, William B. -- 1795-1876 -- Correspondence; Taylor, William J. R. -- 1823-1891 -- Correspondence; Witherspoon, T. D. -- 1836-1898 -- Correspondence; Wood, James, -- 1799-1867 -- Correspondence; Baird family; Confederate States of America. -- Army -- Religious life; American Bible Society; Bible -- Societies, etc. -- Virginia; Presbyterian Church; Presbyterian Church -- Doctrines; United States -- History -- Civil War, 1861-1865 -- Medical care; United States -- History -- Civil War, 1861-1865 -- Religious aspects; Authors; Clergy